Enantioselective SERS sensing of pseudoephedrine in blood plasma biomatrix by hierarchical mesoporous Au films coated with a homochiral MOF; Biosensors and Bioelectronics; Vol. 180 - Guselnikova O. A. Olga Andreevna; Lim H. Hyunsoo; Na J. Jongbeom; Eguchi M. Miharu; Kim Hyun-Jong; Elashnikov R. Roman; Postnikov P. S. Pavel Sergeevich; Svorcik V. Vaclav; Semyonov O. V. Oleg Vladimirovich; Milyutina (Miliutina) E. V. Elena Vadimovna; Lyutakov O. Oleksy; Yamauchi Yu. Yusuke (2021, 2021)
Title screen